(untitled) (Research, Society and Development, 2021)
Acca sellowiana (O. Berg) Burret (feijoa) a fruit native to southern Brazil, with high potential for cultivation, especially for family farmers, with positive prospects for adaptation compared to other commercial fruit. The main disease of the crop is anthracnose caused by the fungus Colletotrichum spp., Which does not have phytosanitary products registered for its control. The objective of this work was to verify the antifungal activity in vitro of different botanical fermentates on the development of the phytopathogen Colletotrichum fructicola. Inhibition of mycelial growth was evaluated in vitro by measuring the perpendicular diameter to determine the percentage of inhibition of fungal growth in triplicate. The treatments consisted of botanical fermented Schinus terebinthifolia, Psisum sativum, Tagetes minuta, Trifolium pratense, Ilex paraguarienses, Vernonanthura tweediana, Prunus myrtifolia and Amaranthus hybridus, to be evaluated in concentrations of 10, 20 and 40% and witness. The main phenolic compound identified via HPLC was gallic acid from the fermented S. terebinthifolia. It was possible to verify that the fermentation of S. terebinthifolia at a concentration of 40% totally inhibited the development of Colletotrichum fructicola. The other fermentates evaluated in this work did not demonstrate a satisfactory effect on this phytopathogenic fungus.